Spoken Art: Amy Lowell's Dramatic Poetry and Early Twentieth-Century Expressive Culture - Simone Knewitz (Current Objectives of Postgraduate American Studies, 2012)
This essay rereads Amy Lowell's dramatic poetry, which has been unduly neglected in literary criticism. Setting the poems in relation to high modernism as well as to the contemporary expressive culture movement—a movement emphasizing the role of the individual in the act of communication—it argues that Lowell's poetry has to be reconsidered as a spoken art.